Identify Problems that Students of The University of Dohuk / Faculty of Educational Sciences which are Faced in order to Make their Search Project Graduation in order yo their Perspective - Ibrahim, Alan J.; Aldirshoy, Abdulmaiman A. (Humanities Journal of University of Zakho, 2017)
This study is aimed to identify problems that students of the University of Dohuk / Faculty of educational sciences which are faced in order to make their Search project graduation in order to their perspective, and know their views depending on gender variable. The population of the present study included of whole students of fourth stages in University of Dohuk school of Educational Sciences between the years 2014/2015. The sample of study is chosen randomly which are including 104 students. Search questionnaire is adopted and developed by the researchers. And after collected the data from the sample of study and analyzed them, it was showed that t-test for two independent samples, and other statistics such as operations Kalost likely relative weight, results presented that the most common problems experienced by students, which appear larger in their expected size, that is included in. - Lack of Kurdish sources in the university library. - Names of research project and those who supervisor them are Delay in announcing. - Lack of knowledge of students to using appropriate statistical methods. - Lack of some teachers in department is not interested to judge validity of the search tools. - The weakness of Internet service at the university. - The weakness of some supervisors to follow-up steps of preparation search project graduation And also, the results are showed that there were no statistical differences between the averages of student’s views according to the gender toward the problems that they face to them. At the end of this study the researcher recommended to do more hard work seriously in order to increase the number of written sources in Kurdish language. And work hardly to prepare the name of research projects at the beginning of the new study year. As well as, to make a good plan for this including preparing all staff of supervisors and students and train them on methodology of scientific research especially in the field of statistics.